Isolation of genes related to abscisic acid production in Botrytis cinerea TB‐3‐H8 by cDNA‐AFLP. (1st March 2013) - Gong, Tao; Shu, Dan; Zhao, Ming; Zhong, Juan; Deng, Hong‐Yuan; Tan, Hong
<x xml:space="preserve">Abstract</x> Abscisic acid (ABA) plays important roles in many aspects of plant growth and development. Botrytis cinerea TB‐3‐H8, a high‐yield strain of ABA, was used to elucidate the molecular mechanisms of ABA production in the present work. cDNA‐amplified fragment length polymorphism (cDNA‐AFLP) technique was applied to isolate genes differentially expressed between ABA high and low‐yield conditions. This resulted in the identification of 856 differentially expressed transcript‐derived fragments (TDFs). Forty‐five TDFs that displayed obvious up‐regulated expression profiles in the ABA high‐yield condition were sequenced. Based on BlastX in NCBI, 31 TDFs were assumed to have homology with genes encoding proteins with known functions. According to molecular function of gene ontology (GO) analysis, the 31 TDFs were categorized to proteins with enzyme catalytic activities, transcription factor activities, transporter activities, and kinds of binding activities. Further confirmation of the differential expression of these sequences was carried out by performing semi‐quantitative reverse transcription polymerase chain reaction (RT‐PCR) on 10 randomly selected TDFs. Five up‐regulated genes were selected to analyze the expression profiles using real‐time PCR. This study enriches our knowledge of the molecular basis for ABA biosynthesis in B. cinerea TB‐3‐H8.